ECOLOGICAL MONITORING OF MOSS AND LICHEN VEGETATION IN THE SYOWA STATION AREA, ANTARCTICA (15th Symposium on Polar Biology) - カンダ, ヒロシ; イノウエ, マサカネ; KANDA, Hiroshi; INOUE, Masakane (National Institute of Polar Research, 1994)
P(論文) The ecological monitoring of moss and lichen vegetation was carried out in the Yukidori Valley, Langhovde, East Antarctica. The valley area was approved as a Site of Special Scientific Interest (SSSI) in 1987. In addition to the two permanent photo points for lichens set up in 1975, all lichen species in 23 quadrats and moss species in 24 quadrats were determined and ecologically described. No increase of lichen growth was detected over periods of 5 and even 14 years, and change in the moss vegetation is hardly detectable after three years. In the moss vegetation, the relations between the surface condition, epiphytic organisms like cyanobacteria and imperfect lichens, or sand cover are discussed. The distribution pattern of mosses and lichens in the Langhovde region were shown. Vegetation is very sparse or absent in the north and northern-east part of the ice-free area. The pattern is probably influenced by wind-blown salt spray. The current abundance and spatial distribution of key species and environmental factors provides essential baseline data for long-term monitoring of local and global impacts on the non-marine biota of the Langhovde regions. departmental bulletin paper